Correlation of excess salt intake identified by the survey with urine sodium level and blood pressure: data of ESSE-RF study - Yu. A. Balanova; V. A. Kutsenko; S. A. Shalnova; A. E. Imaev; A. V. Kapustina; G. A. Muromtseva; S. E. Evstifeeva; N. S. Karamnova; S. A. Maksimov; E. B. Yarovaya; O. M. Drapkina; A. N. Redko; et al. (Российский кардиологический журнал, 2020)
Aim. To study the association of blood pressure (BP) and hypertension (HTN) with salt intake estimated by the survey and the urinary Na+ concentration among men and women 25-64 years old, examined within the ESSE-RF and ESSE-RF-2 studies.Material and methods. Representative samples of the Russian population aged 25-64 years were examined. At the first phase in 2012-2014, 21,888 people (men — 38,2%) were included, and at the second phase in 2017 — 6,714 people (men — 44,7%). The response rate was 80%. We used standard questionnaire. Adding more salt and the consumption of salted foods (sausages, deli meats, and pickled foods) in the criteria “daily or almost daily” was considered excess salt intake (ESI). BP measurement was carried out in a sitting position on the right hand. BP was measured twice with an interval of about 2-3 minutes. HTN was diagnosed at a systolic BP (SBP) ≥140 mm Hg and/or diastolic BP ≥90 mm Hg, or in case of antihypertensive therapy. In ESSE-RF-2, an analysis of the morning urine was additionally performed. Na+ was determined using the EX-Ds ion-selective electrolyte analyzer. All participants were stratified by the quintiles of urine sodium level. Data analysis was performed using the software package R 3.6.1. The models of linear and logistic regression were used. The differences were considered at p<0,05.Results. The average level of SBP significantly increases with an increase in Na+ in urine: 1,04 (0,60-1,48) mm Hg for the quintile of sodium distribution (p<0,001), the odds of HTN increases by 1,11 (1,05-1,17) times for the quintile (p<0,001). Questionnaire components of ESI are also significantly related to urinary Na+ levels. The consumption of sausages and deli meats has the greatest effect, causing an increase in the average Na+ level by 11,59 (7,06-16,12) mmol/l (p<0,001). The applied point scale is significantly related to urine sodium level and predicts HTN no worse than Na+ in the urine (p=0,15 for the difference hypothesis). One point on the scale increases the Na+ level by an average of 7,51 (5,01-10,02) mmol/l, SBP by an average of 0,74 (0,41-1,07) mm Hg and the odds of HTN by 1,1 (1,06-1,15) times (p<0,001 for all).Conclusion. In the pattern of ESI components, processed meat and sausage products take first place in terms of association strength with urine sodium. The questionnaire used to assess the proportion of people with ESI can be recommended for assessing this risk factor during screening. ESI detected by the questionnaire is associated with elevated BP and urinary Na+ values.